In-utero exposure to zidovudine-containing antiretroviral therapy and clonal hematopoiesis in HIV-exposed uninfected newborns. (1st August 2021) - Lin, Shu-Hong; Wang, Youjin; Hartley, Stephen W.; Karyadi, Danielle M.; Lee, Olivia W.; Zhu, Bin; Zhou, Weiyin; Brown, Derek W.; Beilstein-Wedel, Erin; Hazra, Rohan; Kacanek, Deborah; Chadwick, Ellen G.; et al.
Abstract : Objective: Zidovudine (ZDV) has been extensively used in pregnant women to prevent vertical transmission of HIV but few studies have evaluated potential mutagenic effects of ZDV during fetal development. Design: Our study investigated clonal hematopoiesis in HIV-exposed uninfected (HEU) newborns, 94 of whom were ZDV-exposed and 91 antiretroviral therapy (ART)-unexposed and matched for potential confounding factors. Methods: Utilizing high depth sequencing and genotyping arrays, we comprehensively examined blood samples collected during the first week after birth for potential clonal hematopoiesis associated with fetal ZDV exposure, including clonal single nucleotide variants (SNVs), small insertions and deletions (indels), and large structural copy number or copy neutral alterations. Results: We observed no statistically significant difference in the number of SNVs and indels per person in ZDV-exposed children (adjusted ratio [95% confidence interval, CI] for expected number of mutations = 0.79 [0.50–1.22], P = 0.3), and no difference in the number of large structural alterations. Mutations in common clonal hematopoiesis driver genes were not found in the study population. Mutational signature analyses on SNVs detected no novel signatures unique to the ZDV-exposed children and the mutational profiles were similar between the two groups. Conclusion: Our results suggest that clonal hematopoiesis at levels detectable in our study is not strongly influenced by in-utero ZDV exposure; however, additional follow-up studies are needed to further evaluate the safety and potential long-term impacts of in-utero ZDV exposure in HEU children as well as better investigate genomic aberrations occurring late in pregnancy. Abstract : Supplemental Digital Content is available in the text